2015
DOI: 10.1515/pjct-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of dimethyl carbonate and propylene glycol using potassium bicarbonate as catalyst in supercritical CO2

Abstract: The improved one-pot synthesis of dimethyl carbonate and propylene glycol from propylene oxide, supercritical carbon dioxide, and methanol with potassium bicarbonate as the catalyst has been reported in this paper. As far as we know, it is the fi rst time to use potassium bicarbonate only as the catalyst in the production process which is simple and cheap. Satisfactory conversion rate of propylene oxide and yield of the products could be achieved at the optimized conditions with quite a small amount of by-prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…3.1 Direct synthesis of DMC using molecular sieve (3A) and combination of dehydrating agents Thermodynamic limitations and/or catalyst deactivation due to water formation during DMC direct synthesis makes this reaction unfavorable resulting in low DMC yield. 5,24,25 Aiming to evaluate the effect of dehydrating agents (chemical or physical) on the yield of DMC obtained by direct synthesis reaction CH 3 OK was used as catalyst and CH 3 I as promoter. Table 1 presents methanol conversion, DMC selectivity and DMC yield values, reaction parameters and Tukey test results used to evaluate statistical equality between samples (see letters a to g in conversion column, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…3.1 Direct synthesis of DMC using molecular sieve (3A) and combination of dehydrating agents Thermodynamic limitations and/or catalyst deactivation due to water formation during DMC direct synthesis makes this reaction unfavorable resulting in low DMC yield. 5,24,25 Aiming to evaluate the effect of dehydrating agents (chemical or physical) on the yield of DMC obtained by direct synthesis reaction CH 3 OK was used as catalyst and CH 3 I as promoter. Table 1 presents methanol conversion, DMC selectivity and DMC yield values, reaction parameters and Tukey test results used to evaluate statistical equality between samples (see letters a to g in conversion column, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, this synthetic route presents thermodynamic limitations, and the use of dehydrating agents must be employed in order to shift the equilibrium . Several homogeneous and heterogeneous catalysts have been studied to convert CO 2 and methanol into DMC, including AC-Fe (iron salts impregnated on activated carbon), Cu–Ni/graphene, K 2 CO 3 , and metal oxides, such as ZrO 2 , Fe 0.7 Zr 0.3 O y , and CeO 2 , , among others.…”
Section: Introductionmentioning
confidence: 99%
“…Many metal oxide nanomaterials have been considered as efficient heterogeneous catalysts for the direct synthesis of DMC from CO 2 and methanol. Thus, CeO 2 is an exciting choice because of its high density of basic sites, high oxygen storage capacity (OSC), oxygen mobility, and good redox properties, which render excellent catalytic properties for DMC production. , We have demonstrated that different cerium precursors influence the morphology of the synthesized nanostructured CeO 2 , modifying the exposed planes, basicity, and concentration of oxygen vacancies . This later property also plays a crucial role in the catalytic activity of DMC production from CO 2 and methanol. However, pure CeO 2 presents poor thermal stability and readily sinter at high temperatures. , Thus, ceria-supported catalysts are preferred over individual components due to their combined properties, enabling them to overcome the limitations of single-phase materials. , Reports have shown that adding transition metal oxides into the CeO 2 structure improves the catalytic performance of the mixed oxides compared to the bare ones. , For example, Tomishige et al observed an improvement in thermal stability and redox properties upon adding ZrO 2 to the CeO 2 structure for the DMC synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[89]. Diffraction peaks around 59 • and 62.5 • correspond to (511) and (440) planes of Fe 3 O 4[88,[90][91][92][93]. Besides, a peak near 25• corresponds to goethite (120) (JCPDS Card n • .…”
mentioning
confidence: 99%